2019
DOI: 10.1021/acs.energyfuels.8b03809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citric Acid Addition Method on the Activity of NiMo/γ-Al2O3 Catalysts in Simultaneous Hydrodesulfurization and Hydrodenitrogenation Reactions

Abstract: Two NiMo catalysts were prepared by different methods using citric acid to assess the effects of preparation method on dibenzothiophene hydrodesulfurization (HDS) and simultaneous HDS and hydrodenitrogenation: co-impregnation and post-treatment. Characterization of oxide catalysts was performed by nitrogen physisorption, X-ray diffraction, and temperature-programmed sulfidation, while sulfided samples were characterized by temperature-programmed reduction (TPR-S) and NO chemisorption. The catalytic evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[20] Moreover, these catalysts can also be boosted by adding another element, such as phosphorus [21,22] or a chelating agent (e. g., citric acid). [23,24] Biller et al [25] employed NiMo/Al 2 O 3 and CoMo/Al 2 O 3 sulfide catalysts to upgrade algal HTL bio-oils and reported that both catalysts showed similar activity during hydroprocessing. Later, Guo et al [26] compared commercial NiMo/Al 2 O 3 and NiW/Al 2 O 3 and concluded that NiMo performed better in removing oxygen and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Moreover, these catalysts can also be boosted by adding another element, such as phosphorus [21,22] or a chelating agent (e. g., citric acid). [23,24] Biller et al [25] employed NiMo/Al 2 O 3 and CoMo/Al 2 O 3 sulfide catalysts to upgrade algal HTL bio-oils and reported that both catalysts showed similar activity during hydroprocessing. Later, Guo et al [26] compared commercial NiMo/Al 2 O 3 and NiW/Al 2 O 3 and concluded that NiMo performed better in removing oxygen and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…These nanomaterials are usually supported on γ‐alumina and are promoted by nickel or cobalt [20] . Moreover, these catalysts can also be boosted by adding another element, such as phosphorus [21,22] or a chelating agent (e. g., citric acid) [23,24] …”
Section: Introductionmentioning
confidence: 99%
“…In the early 2000s, a modified workflow gained traction since it yielded catalysts of higher activity. In this workflow, organic additives, such as glycols, ethylenediaminetetraacetic acid (EDTA), or nitrilotriacetic acid (NTA), were added to the catalyst formulation. Since these additives would decompose or oxidize under typical calcination conditions (400 °C in air), the calcination step was omitted. The effect of organic additives on catalytic performance has been explored in numerous studies, linking changes in structure, density, and stability of the active phase to performance. , These uncalcined catalyst types show a low tendency to form Mo–O–Al bonds, which advances the formation of type II catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the supported NiMo catalysts are prepared by conventional wetness impregnation. The active metal species are simultaneously or sequentially loaded on premade supports. The improved dispersion of metal oxide at high metal loading resulting from strong metal–support interaction may decrease the sulfidation degree of metal species, which is unfavorable for the HDN reaction.…”
Section: Introductionmentioning
confidence: 99%